Burkholderia cepacia infection in the neonatal unit: a cautionary tale of contaminated EEG skin preparation - Chua, I-Ly Joanna; Blyth, Chris; Porter, Michelle; Minney-Smith, Cara; Merritt, Adam; Brennan, Brittany; Farrar, Cristina; Pelumbo, Linda; Engelbrecht, Danielle; Nicolaou, Lisa (International Journal of Infection Control, 2024)
Burkholderia cepacia isolated from a scalp wound of a neonate prompted investigation to identify potential sources. The same organism was isolated from numerous batches of gel used to prepare skin prior to electroencephalography (EEG), prompting a recall of this product. This case highlights the potential for contamination of equipment and products used for EEG.